Extraction and characterization of liver oil from silky shark - Anhar Rozi; Sugeng Heri Suseno; Agoes Mardiono Jacoeb (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Silky shark liver was 10-15% of its body mass and 50% of oil is contained in the liver. The aimed ofthis study was to determine heavy metal content, fatty acid profile on raw material, extraction of its oil, andparameter of oxidation. The method of heavy metal test stated on the SNI and fatty acid analysis referredto AOAC. The extraction was oven methode at 50, 60, 70, and 80°C in 8 hours. Cadmium (Cd) as thehighest heavy metal content with 0.88±0.01 ppm, SFA was 18.46% composed by palmitic acid dominantly(12.59%). The MUFA was 24.54 % with the highest oleic acid (17.86%). PUFA was 19.11 % that consist ofDHA (14.35%) as the most abundantly present while EPA was 1.50%. Shark liver oil which was extractedat 50°C had the highest yield (24.47%). The oxidation of silky shark liver oil extraction indicated the besttreatment at 50°C with peroxide value (PV), p-Anisidine value (p-AV), percentage of free fatty acid (% FFA),acid value (AV), and total oxidation (TOTOX) were 7.26±1.27 mEq/kg, 16.79±0.28 mEq/kg, 5.47±0.12%,10.88±0.25 mg KOH/kg, and 31.31±2.26 mEq/kg respectively.